How to start a new research project: a guideline for thesis writers - Lueg, Rainer (Proceedings of Pragmatic Constructivism, 2011)
This paper suggests how to start a new research project. As such, it can be used as a guideline by less experienced thesis writers that are currently finishing their studies on the undergraduate, graduate, or postgraduate level. The basis for the suggestions are publications that link topically to research projects I have started during my theses, revised with co-authors, and published in journals, books, conference proceedings, or edited volumes.